Endogenous Expression of Galectins and Tissue Binding Profile of a Galactose Specific Plant Lectin in Cervical Intra Epithelial Neoplasia: It’s Significance to Assess the Malignant Potential - S. Nair2, L.S. Smitha2, P. Remani2, K. Sujathan1*, Thara Somanathan1, Laija (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Galectins are a family of low molecular weight β-galactoside binding proteins with functions in cell growth, cell activation, cell–cell, cell–matrix adhesion including binding to carcinoembryonic antigen, laminin and metalloprotenase. Higher endogenous expression of Galecin-3 (Gal3) and Galectn-1(Gal-1) has been found in malignancies. Several other galactose specific lectin binding patterns have been reported to differentiate dysplastic epithelium from normal epithelium. Galectin expression studies in cervical epithelium are comparatively less. We analyzed the endogenous expression of Gal-1, Gal-3 and the binding profile of a plant lectin with identical sugar specificity in cervical intra epithelial neoplasia (CIN) to evaluate its significance as a marker to assess the malignant potential of CIN. Sections from 66 archival samples of colpscopic biopsy were analyzed using the standard immunohistochemical method using polyclonal antigalectin antibodies and HRP conjugated snake gourd lectin using DAB as the chromogen. The expression pattern was assessed semi quantitatively and analysed statistically to see the significance as a predictor of the malignant potential of CIN. Galectin expression was observed in cytoplasm and cell membrane. Neither the galectins nor the plant lectin seemed to have any role in predicting malignant potential if cervical intra epithelial lesion. As these lectins express more in differentiated epithelium this can be suggested as markers of differentiation which may have some significance in tumor pathology.